The associations between dietary fibers intake and systemic immune and inflammatory biomarkers, a multi-cycle study of NHANES 2015–2020 - Qi, Xiangjun; Li, Yanlong; Fang, Caishan; Jia, Yingying; Chen, Meicong; Chen, Xueqing; Jia, Jie (Frontiers in Nutrition, 2023)
Background: This study aims to investigate the associations between dietary fibers intake and systemic immune and inflammatory biomarkers. Methods: This cross-sectional study used data from the National Health and Nutrition Examination Survey (2015–2020). Dietary fibers intake was defined as the mean of two 24-hour dietary recall interviews. The SII, SIRI, NLR, PLR, RA, ferritin, hs-CRP, and WBC count were measured to evaluate systemic immune and inflammatory states of the body. The statistical software packages R and EmpowerStats were used to examine the associations between dietary fibers intake and systemic immune and inflammatory biomarkers. Results: Overall, 14392 participants were included in this study. After adjusting for age, gender, race, family monthly poverty level index, alcohol consumption, smoking status, vigorous recreational activity, body mass index, hyperlipidemia, hypertension, diabetes, and dietary inflammatory index, dietary fibers intake was inversely associated with SII (β = -2.19885, 95% CI: -3.21476 to -1.18294, P = 0.000248), SIRI (β = -0.00642, 95% CI: -0.01021 to -0.00263, P = 0.001738), NLR (β = -0.00803, 95% CI: -0.01179 to -0.00427, P = 0.000284), RA (β = -0.00266, 95% CI: -0.00401 to -0.00131, P = 0.000644), ferritin (β = -0.73086, 95% CI: -1.31385 to -0.14787, P = 0.020716), hs-CRP (β = -0.04629, 95% CI: -0.0743 to -0.01829, P = 0.002119), WBC (β = -0.01624, 95% CI: -0.02685 to -0.00563, P = 0.004066), neutrophils (β = -0.01346, 95% CI: -0.01929 to -0.00764, P = 0.000064). An inverse association between dietary fibers and PLR was observed in the middle (β = -3.11979, 95% CI: -5.74119 to -0.4984, P = 0.028014) and the highest tertile (β = -4.48801, 95% CI: -7.92369 to -1.05234, P = 0.016881) and the trend test (βtrend = -2.2626, 95% CI: -3.9648 to -0.5604, Ptrend = 0.0150). The observed associations between dietary fibers intake and SII, SIRI, NLR, RA, ferritin, hs-CRP, WBC, and neutrophils remained robust and consistent in the sensitivity analysis. No significant interaction by race was found. Conclusion: Dietary fibers intake is associated with the improvement of the parameters of the immune response and inflammatory biomarkers, supporting recommendations to increase dietary fibers intake for enhanced immune health.